Effect of centrifugation time on the optical properties of colloidal silicon nanoparticle. (2018) - Biswas, Susmita; Nandi, Anupam; Dhara, Arnab; Baral, Apurba; Saha, Hiranmay; Mukherjee, Nillohit; Hossain, Syed Minhaz
Abstract: We report synthesis of colloidal suspension of silicon (Si) nanoparticle (NP) with native silicon dioxide (SiO2 ) layer by mechanical milling. Different size distribution of Si NPs in the colloid has been obtained by varying the centrifugation time. Width of the particle distribution curve of Si NPs was found to decrease with increasing centrifugation time of the colloidal suspensions, which has been established from the FESEM analysis. The variation of particle size also put its signature in the photoluminescence (PL) properties of the prepared materials.